PERSEPSI MAHASISWA SURABAYA TERHADAP PEMBERITAAN VAKSINASI COVID-19 PADA SOSIAL MEDIA INSTAGRAM - Rista Dwi Lestari (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2021)
Abstract In order to prevent COVID-19 spread, Indonesian government has declared a prevention strategy of vaccination towards the community at the end of this year. Vaccination programs eventually contribute pros and cons which responding to upcoming executions. Experts and community representatives have to explain the emergence of vaccines throughout their social media accounts. During the pandemic, social media has been working effectively as a better option to spread knowledge and regulations of the viruses. Accessibility of information-contained digital technology, particularly on social media platforms such as Instagram, has a significant impact on public perceptions. This research looked at how students in Surabaya responded to information about the Covid-19 vaccine on dr.Tirta's Instagram page. using a qualitative approach and data collection techniques by conducting online interviews. Based on result using 8 college student participants in the 20-26 years age group, 6 out of 8 participants agrees on vaccination which posted on dr. Tirta's Instagram fully educates them because the information is accompanied by an appropriated data which motivates the students willing to do vaccinate Covid-19. The information of Covid-19 on dr. Tirta's Instagram creates a powerful impact on students' perception in term of Covid-19 vaccination. Thus, it makes them glad to do the vaccination. Keywords: Covid-19 Pandemic, Social Media, Perception